The Effect of the Free Nutritious Meal Program on the Nutritional Status and Academic Performance of Elementary School Students in the Catchment Areas of the Langgudu and Monta Community Health Centers - Eka Puzi Lestari; M Noris; Aris Iwansyah; Al Khair (Syifa'Medika, 2026)
The Free Nutritious Meal Program (MBG) is one of the Indonesian government's initiatives to improve the nutritional status and educational quality of elementary school students. Adequate nutritional status plays a crucial role in supporting children's physical growth, cognitive development, concentration, and academic performance. This study aimed to analyze the effect of the Free Nutritious Meal Program (MBG) on the nutritional status and academic performance of elementary school students in the catchment areas of the Langgudu and Monta Community Health Centers. This study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. A total of 100 students participated in the study, comprising an experimental group from SDN Inpres Doro O'o, Langgudu District, and a control group from SD Inpres Tanjung Baru, Monta District. Data were analyzed using the Wilcoxon Signed-Rank Test, Fisher's Exact Test, Paired Samples t-test, and Independent Samples t-test with a significance level of ? = 0.05. The results demonstrated that the Free Nutritious Meal Program (MBG) had a significant effect on improving students' nutritional status, as indicated by the Wilcoxon Signed-Rank Test (p < 0.003) and Fisher's Exact Test (p < 0.001). The program also significantly improved students' academic performance, as evidenced by higher mean test scores in the experimental group and the results of the Independent Samples t-test (p < 0.001). The experimental group exhibited greater improvements in both nutritional status and academic performance than the control group. In conclusion, the Free Nutritious Meal Program (MBG) significantly improves the nutritional status and academic performance of elementary school students. The program should be sustained and expanded while being supported by strengthened nutrition education in schools and families to optimize students' health and educational outcomes.